2022
DOI: 10.1111/1744-9987.13812
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic risk factors in patients with refractory heart failure treated with continuous veno‐venous hemofiltration

Abstract: Introduction Investigation of the prognostic factors in patients with refractory heart failure (HF) undergoing continuous veno‐venous hemofiltration (CVVH). Methods Clinical data of 146 patients with refractory HF between May 2018 and December 2020 were retrospectively analyzed and divided into survival and death groups according to the prognosis. Vital signs, inflammatory markers, and renal function parameters were compared before and after treatment. Results Central venous pressure levels were lower, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Such patients have more cardiovascular risk factors such as diabetes and hypertension, so their prognosis is relatively poor. Relevant studies have shown that cardiac remodeling accounts for an important pathogenesis of HF [6,7] . Oxidative stress, activation of the neuroendocrine system, inflammatory response, abnormal hemodynamics and overloading of the heart lead to increased ventricular wall pressure.…”
mentioning
confidence: 99%
“…Such patients have more cardiovascular risk factors such as diabetes and hypertension, so their prognosis is relatively poor. Relevant studies have shown that cardiac remodeling accounts for an important pathogenesis of HF [6,7] . Oxidative stress, activation of the neuroendocrine system, inflammatory response, abnormal hemodynamics and overloading of the heart lead to increased ventricular wall pressure.…”
mentioning
confidence: 99%